Chemical Glycosylation and Its Application to Glucose Homeostasis-Regulating Peptides - Chandrashekar, Chaitra; Hossain, Mohammed Akhter; Wade, John D. (Frontiers in Chemistry, 2021)
Peptides and proteins have a myriad of functional roles necessary for life. Because of their exquisite receptor specificity and low toxicity, these fascinating biomolecules have redefined the field of therapeutics. However, their enormous therapeutic potential is limited by their complex composition that gives rise to several challenges in drug development ranging from solubility, stability, aggregation, low bioavailability, and poor pharmacokinetics. Currently, a range of small therapeutic peptides to large proteins including antibodies are in clinical use. Much effort towards enhancing the biochemical properties and pharmacokinetics of peptides and proteins has been undertaken over the years. This includes the introduction of several natural and non-natural modifications such as PEGylation, lipidation, cyclization, non-natural amino acids, and glycosylation. The latter modification is considered to be one of the most useful as it is known to contribute in increasing the stability, to improve solubility, and increase the circulating half-life of these biomolecules. In this mini-review, we highlight the importance of glycosylation for improving naturally non-glycosylated, therapeutically essential insulin and related peptides that are used in the treatment of diabetes.